The Relationship between Environmental Disclosure and Financial Performance of Industrial companies with Using a New Theory: Literature Review - Al-Waeli , Abbas Jumaah; Khalid, Azam Abdelhakeem; Ismail, Zuriadah; Idand, Hayder Zghair (The journal of contemporary issues in business and government, 2021)
This paper primarily examines the link between the environmental disclosure of industrial companies in Iraq and their financial performance. The inductive approach used in this paper entails surveying, studying, comparing and summarizing all papers published in prominent accounting journals in the past nineteen years. The paper found that environmental disclosure is weak in Iraq compared to developing countries in the analyzed studies. It also found that financial performance and environmental disclosure have a more positive relationship (61.29%) than negative (38.71%). The researchers used the accountability theory as a new theory in determining the link between both variables. Hence, this paper attempts to determine the link between environmental disclosure and financial performance among industrial companies in Iraq using the accountability theory.